Seasonal variation in Arctic marine mammal acoustic detection in the northern Bering Sea. Issue 2 (24th December 2019) - Chou, Emily; Antunes, Ricardo; Sardelis, Stephanie; Stafford, Kathleen M.; West, Leigh; Spagnoli, Christopher; Southall, Brandon L.; Robards, Martin; Rosenbaum, Howard C.
Abstract: Declines in Arctic sea ice cover are influencing the distribution of protected endemic marine mammals, many of which are important for local Indigenous Peoples, and increasing the presence of potentially disruptive industrial activities. Due to increasing conservation concerns, we conducted the first year‐round acoustic monitoring of waters off Gambell and Savoonga (St. Lawrence Island, Alaska), and in the Bering Strait to quantify vocalizing presence of bowhead whales, belugas, walruses, bearded seals, and ribbon seals. Bottom‐mounted archival acoustic recorders collected data for up to 10 months per deployment between 2012 and 2016. Spectrograms were analyzed for species‐typical vocalizations, and daily detection rates and presence/absence were calculated. Generalized additive models were used to model call presence as a function of time‐of‐year, sea surface temperature, and sea ice concentration. We identified seasonality in call presence for all species, corroborating previous acoustic and distribution studies, and identified finer‐scale spatiotemporal distribution via occurrence of call presence between different monitoring sites. Time‐of‐year was the strongest significant effect on call presence for all species. These data provide important information on Arctic endemic species' spatiotemporal distributions in biologically and culturally important areas within a rapidly changing Arctic region.